WEAK WRIT AREAS IN PAKISTAN – CHALLENGE FOR INTERNAL SECURITY GOVERNANCE - Nayyar Naseer; Syed Waqas Ali Kausar (Journal of Peace, Development and Communication, 2024)
This article examines the structural governance flaws that have considerably affected the internal security governance in Pakistan. One of the main governance flaws is the possession of areas with poor writ of the government and no formal policing that has seriously affected the lives of citizens of Pakistan. Few of these areas were inherited at the time of Pakistan’s independence from British India in 1947 including seven Federally Administered Tribal Areas (FATA) called “Agencies”, and six Frontier Regions (FRs). Moreover, Malakand Division with the status as Provincially Administered Tribal Areas (PATA) were independent states till 1969 where hardline Islamic parties demanded the implementation of Islamic rule and Category “B” areas of Balochistan with weak state writ and absence of a defined police system. Some weak governed areas like “Tri-Border Belt” and even portions of Karakoram Highway (KKH) have emerged where criminal elements operated with impunity. The article takes into account first and second-hand sources tracing out the peculiarities of weak writ areas highlighting neglect of successive governments and their effects on Pakistan’s internal security especially after the event of 9/11. Spillover of Afghan instability resulted into use of these areas by terrorists escaping from Afghanistan and the formation of a defunct terrorist movement called Tehreek-e-Taliban Pakistan (TTP) which seriously disturbed the fibres of internal stability governance in Pakistan. The article aims to examine the impact of weak governance in Pakistan’s Tribal and border regions on internal security and to assess the role of military interventions, a non-preferred option in stabilizing security in these areas. It was only after launching numerous military actions that the situation got relatively stabilized for internal security. There is a need for long-term measures to bring sustainable stability in weak-governed areas of the country.